2009
DOI: 10.1186/1477-7827-7-48
|View full text |Cite
|
Sign up to set email alerts
|

Administration of follitropin alfa and lutropin alfa combined in a single injection: a feasibility assessment

Abstract: Background: Gonadotrophins are routinely administered in assisted reproductive technology (ART) treatment protocols. Recombinant human follicle-stimulating hormone (r-hFSH; follitropin alfa) and recombinant human luteinizing hormone (r-hLH; lutropin alfa) can be administered individually or in a fixed combination. The ability to vary the FSH to LH dose ratio in a single injection without compromising the bioactivity of either gonadotrophin or generating losses of active principle is important for physicians an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
0
7
0
1
Order By: Relevance
“…2001; Kanitz et al. 2002), and, in human fertility, can be patient‐dependent with factors such as age, parity, and overall ovarian function impacting results (Agostinetto 2009). Supplying a dual‐active gonadotropin may alleviate some of the problems encountered with administering only FSH and allow the desired ratio of FSH/LH to be achieved using one molecule.…”
Section: Recombinant Gonadotropin Productionmentioning
confidence: 99%
“…2001; Kanitz et al. 2002), and, in human fertility, can be patient‐dependent with factors such as age, parity, and overall ovarian function impacting results (Agostinetto 2009). Supplying a dual‐active gonadotropin may alleviate some of the problems encountered with administering only FSH and allow the desired ratio of FSH/LH to be achieved using one molecule.…”
Section: Recombinant Gonadotropin Productionmentioning
confidence: 99%
“…14,15 A mixture of follitropin alpha and lutropin alpha (follitropin alpha/lutropin alpha 150 IU/75 IU) has been recently commercially available in a single product called Pergoveris TM (Merck Serono). 16 Biopatency studies have confirmed that the new drug is treated in the body similarly as if each product were administered separately. 14,16 This combination could be of value for the stimulation of follicular development in infertile women with severe endogenous FSH and LH deficiency, using a single daily injection.…”
Section: Introductionmentioning
confidence: 89%
“…16 Biopatency studies have confirmed that the new drug is treated in the body similarly as if each product were administered separately. 14,16 This combination could be of value for the stimulation of follicular development in infertile women with severe endogenous FSH and LH deficiency, using a single daily injection. 17…”
Section: Introductionmentioning
confidence: 89%
“…Gonadotrophins used for conventional ovulation induction are either urinary or recombinant products. Urinary human menopausal gonadotrophins contain a combination of FSH 75 iu and LH 75 iu, while the recombinant preparations usually contain either FSH or LH activity, although newer preparations with combined recombinant FSH and LH in a single injection are now available . In women with hypothalamic hypogonadism, recombinant FSH alone stimulates follicular growth, but results in inadequate estrogen production, confirming the need for LH to fulfil the ‘two cell, two gonadotrophin’ requirement for ovarian steroidogenesis (Figure ) …”
Section: Who Group I Disorders – Hypothalamic Pituitary Failure (Hypomentioning
confidence: 99%